The determinants of unemployment rate in Malaysia / Nurul Fatin Amalina Mohd Yusof - Mohd Yusof, Nurul Fatin Amalina (Faculty of Business and Management, 2015)
Unemployment is one of the important macroeconomic issues that all government and economic face. A change in economy can occur anytime and may affect the development of country as well as unemployment rate. It has both social and economic implications for all economies and the government take an action and try to adopt policies that will help in increasing employment rate. Therefore, the main purpose of this research was to examine the determinants that affect the unemployment rate in Malaysia. The data was collected from Datastream and EIU country data from 2003 untill 2014 (quarterly basis). The multiple linear regressions was used to analyze the significant relationship between independent variable ( oil prices, inflation rate, gross domestic product and exchange rate volatility) towards dependent variable (unemployment rate). The findings of this study was suggested that Malaysia‘s economic growth is determined by changes in oil price, inflation rate, gross domestic product and exchange rate volatility towards unemployment rate.